A Comparison Between the HORIBA Yumizen H500 Point-of-Care Hematology Analyzer With a 5-Part White Cell Differential and the HORIBA Pentra 120. Issue 2 (June 2017) - Woolley, Timothy; Davies, Bethan Jade; Rutter, Emma; Probert, Charlotte; Fitzgerald, Leanne; Relf, William
Abstract : Abstract: The release of new and innovative platforms has helped the point-of-care testing market to grow and cement its wider uptake in various clinical settings. Driven by the introduction of novel patient pathways often centered on clinics remote from a laboratory, the need for laboratory grade parameters and results from point-of-care analyzers is now critical. In this paper, we compare the 5-part white blood cell (WBC) differential from HORIBA Medicals mainline hematology analyzer, the Pentra 120, and those provided from the recently released Yumizen H500 point-of-care analyzer. The Yumizen H500 is based on HORIBA's Micros platform and is aimed at the point-of-care/primary care market. The Yumizen H500 is capable of measuring a full blood count (27 parameters) including a 5-part WBC differential using only 20 μL of whole blood in approximately 2 minutes. The analyzer also has both open and closed venous tube options, making it suitable for pediatric and capillary samples as well as easier and safer to use in the point-of-care setting. We found that all full blood count parameters were intra-assay reproducible and compared well with previous precision studies; likewise, the patient R 2 values for neutrophils, lymphocytes, monocytes, and eosinophils also compared well at 0.994 for WBC, 0.952 for neutrophils, 0.942 for lymphocytes, 0.84 for monocytes, and 0.81 for eosinophils. In conclusion, the Yumizen H500 provides reproducible, precise, and accurate results compared with our institute's mainline laboratory analyzers.